Analysis of purchasing decisions through advertising on social media, product completeness and brand image on the Tokopedia application - Sumadi Saputra; Muinah Fadhilah; Agus Dwi Cahya (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the influence of "Advertising on Social Media, Product Completeness and Brand Image on Purchasing Decisions on the Tokopedia Application". The type of research used is quantitative research. The population of this research is Tokopedia application users in Yogyakarta who make a minimum purchase once and have a minimum age of 17 years. The research sample consisted of 100 respondents. This research uses a purposive sampling technique. This research analysis model uses the SPSS 23 application. Data was collected using a questionnaire. The analysis techniques used are Multiple Linear Regression Analysis, Classical Assumption Test, Hypothesis Testing, and Coefficient of Determination. The results of this research show that the variable advertising on social media, brand image has a significant influence and the product completeness variable has no influence on purchasing decisions. Advertising variables on social media, product completeness, and brand image simultaneously influence purchasing decisions.